Implementing Online English Training Program to Improve Teachers’ English Proficiency And Webcam Monitoring Based Tests at a Vocational High School in Bandung, Indonesia - Widia Resdiana; Sari Armiati; Dewi Selviani Yulientinah; Nyi Raden Nuraini Siti Fathonah; Widia Resdiana (Merpati: Media Publikasi Pengabdian Kepada Masyarakat Politeknik Pos Indonesia, 2022)
This Community Service Program at a state vocational high school in Bandung, Indonesia, aims to improve teachers’ English proficiency by conducting English training and the improvements are seen from the pre test and post test of a standardized test namely TOEFL-like. The participants who undertook those tests were 28 teachers coming from different fields of background and they had trainings of TOEFL materials such as Listening, Structure and Written Expressions, and Reading for approximately 24 hours. To find out the significant results of the training, the data from the TOEFL score were analyzed using pre-experiment one group pretest and posttest design. The results of the Program are that the activities of socialization, tests, and trainings were carried out successfully and right on schedule, and the training given to the participants has brought impacts to the increase of the participants’ skill as the score of post test improved significantly. However, some room for improvements in the future is suggested as the result of the questionnaire, such as enriched training materials and longer activities. As for the instructors, they need to improve the elements of enthusiasm and interest during delivering the materials, demonstrating and mastering the training material for future activities.